Effect of moderate irrigation on grape composition during ripening - De la Hera Orts, M.L.=700 1 Martinez Cutillas, A.; Lopez Roca, J.M.; Gomez Plaza, E.
(Es, En)
ilus., 25 ref.
Keywords: VITIS VINIFERA; COMPOSICION QUIMICA; ACIDEZ; ANTOCIANINAS; AZUCARES; COLOR; MADURACION; VINO; RIEGO; ESPAÑA